Dampak Kenaikan Harga Bahan Bakar Minyak (BBM) Terhadap Pasar Modal Setelah Pandemi Covid-19 - Anis Widiyanti Futri; Cahya Juliana; Angga Abdul Rojak; Dedek Kustiawati (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The increase in fuel prices is nothing new for the people of Indonesia. Fuel continues to increase from year to year which is quite significant in the state budget on the state expenditure side. Fuel has become the main need that is needed by the people of Indonesia to fulfill their daily needs. The increase in fuel prices is certain to trigger prices of basic commodities resulting in an inflation rate that triggers the capital market. Inflation has both good and bad effects on the economy. Inflation monitored in Indonesia in recent months shows that covid-19 has an impact on the country's economy, especially in the trade sector consisting of exports, imports, raw resources and capital goods. This study aims to determine the impact of rising fuel oil (BBM) prices on the capital market after the covid-19 pandemic. The data collection technique used in this research is literature study technique.